2019
DOI: 10.1080/13621718.2019.1679963
|View full text |Cite
|
Sign up to set email alerts
|

Material flow during friction hydro-pillar processing

Abstract: Friction hydro-pillar processing (FHPP) is a novel technique that involves solid-state joining of an external plug onto a substrate by plastic deformation. A systematic investigation on material flow during FHPP is required but rarely reported. The present work reports a coupled theoretical and a three-dimensional X-ray computer tomography-based experimental study using a Ti-alloy as a tracer material to realise the material flow during FHPP of a AISI 4140 steel substrate. The cumulative results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The higher temperature isotherms, orange and red contours, tend to concentrate towards the pipe-girth interface and remain around 0.91 ∼ 0.95 times the solidus temperature (T S ) of the base material (Table 2). Landell et al [18] also reported similar range of peak temperatures in friction based joining of steels and other structural materials. A comparison of (Figs.…”
Section: Temperature Distribution and Thermal Cyclesmentioning
confidence: 71%
See 4 more Smart Citations
“…The higher temperature isotherms, orange and red contours, tend to concentrate towards the pipe-girth interface and remain around 0.91 ∼ 0.95 times the solidus temperature (T S ) of the base material (Table 2). Landell et al [18] also reported similar range of peak temperatures in friction based joining of steels and other structural materials. A comparison of (Figs.…”
Section: Temperature Distribution and Thermal Cyclesmentioning
confidence: 71%
“…The same also complies with the hypothesis that no heat generation due to frictional work would occur when the material is adequately softened or melted [20]. Such a friction law has widely been used for modeling of several variants of friction welding processes including rotary friction welding (RFW) [15,16,21], friction stir welding (FSW) [20] and friction hydropillar processing (FHPP) [18]. The values of η h and μ were considered as 0.5 and 0.3, respectively.…”
Section: Theoretical Formulationmentioning
confidence: 79%
See 3 more Smart Citations